Development of scalable electronics for the TORCH time-of-flight detector - Gao, R; Brook, N; Garcia, L; Cowie, E; Cussans, D; Forty, R; Frei, C; Gys, T; Harnew, N; Piedigrossi, D; Van Dijk, M (IOP Publishing, 2015)
The TORCH detector is proposed for the low-momentum particle identification upgrade of the LHCb experiment. It combines Time-Of-Flight and Cherenkov techniques to achieve charged particle separation up to 10 GeV/c. This requires a time resolution of 70 ps for single photons. Existing electronics has already demonstrated a 26 ps intrinsic time resolution; however the channel count and density need improvements for future micro-channel plate devices. This paper will report on a scalable design using custom ASICs (NINO-32 and HPTDC). The system provides up to 8 × 64 channels for a single micro-channel plate device. It is also designed to read out micro-channel plate tubes with charge-sharing technique.